The Oxford handbook of international relations - Reus-Smit, Christian, 1961-.; Snidal, Duncan (Oxford ; New York : Oxford University Press, 2010)
Contents
Includes bibliographical references and indexes.
Keywords: International relations; Uluslararası ilişkiler; World politics; Dünya politikası